STUDENTS PERCEPTION OF USING QUILLBOT TO IMPROVE STUDENTS WRITING SKILLS - Nabila Laila; Ernita Daulay (Indonesian EFL Journal, 2024)
This research aims to analyze students' writing skills using the Quillbot application. This research uses a qualitative research design, the participants are students at State Islamic University of North Sumatra. Data was obtained from questionnaires and interviews. This research focuses on senior semester students at the State Islamic University of North Sumatra. A total of 31 students  participants in this research and 4 students were selected to answer interview questions. The data collection technique used in this research is a non-test technique which comes from two sources, namely questionnaires and in-depth interviews. The results show that most students thought using Quillbot helped them become better academic writers. To put it another way, students see the Quillbot app favorably as a digital tool for writing well. According to the research, all of the participants thought that the Quillbot application could facilitate writing in English. 100% of participants believed that the Quillbot application helped them write more and made fewer mistakes when they did write, while up to 90% of participants thought it could help them write better. Overall, students gave positive responses to the use of Quillbot to help improve their writing skills. This research contributes to the existing literature on improving language learning technology by providing insight into how students use Quillbot to improve students' English writing skills.